Electrical Substrate Elimination in 135 Consecutive Patients With Brugada Syndrome. (May 2017) - Pappone, Carlo; Brugada, Josep; Vicedomini, Gabriele; Ciconte, Giuseppe; Manguso, Francesco; Saviano, Massimo; Vitale, Raffaele; Cuko, Amarild; Giannelli, Luigi; Calovic, Zarko; Conti, Manuel; Pozzi, Paolo; et al.
Abstract : Background—: There is emerging evidence that localization and elimination of abnormal electric activity in the epicardial right ventricular outflow tract may be beneficial in patients with Brugada syndrome. Methods and Results—: A total of 135 symptomatic Brugada syndrome patients having implantable cardiac defibrillator were enrolled: 63 (group 1) having documented ventricular tachycardia (VT)/ventricular fibrillation (VF) and Brugada syndrome–related symptoms, and 72 (group 2) having inducible VT/VF without ECG documentation at the time of symptoms. About 27 patients of group 1 experienced multiple implantable cardiac defibrillator shocks for recurrent VT/VF episodes. Three-dimensional maps before and after ajmaline determined the arrhythmogenic electrophysiological substrate (AES) as characterized by prolonged fragmented ventricular potentials. Primary end point was identification and elimination of AES leading to ECG pattern normalization and VT/VF noninducibility. Extensive areas of AES were found in the right ventricle epicardium, which were wider in group 1 ( P =0.007). AES increased after ajmaline in both groups ( P <0.001) and was larger in men ( P =0.008). The increase of type-1 ST-segment elevation correlated with AES expansion ( r =0.682, P <0.001). Radiofrequency ablation eliminated AES leading to ECG normalization and VT/VF noninducibility in all patients. During a median follow-up of 10 months, the ECG remained normal even after ajmaline in all except 2 patients who underwent a repeated effective procedure for recurrent VF. Conclusions—: In Brugada syndrome, AES is commonly located in the right ventricle epicardium and ajmaline exposes its extent and distribution, which is correlated with the degree of coved ST-elevation. AES elimination by radiofrequency ablation results in ECG normalization and VT/VF noninducibility. Substrate-based ablation is effective in potentially eliminating the arrhythmic consequences of this genetic disease. Clinical Trial Registration—: URL:https://clinicaltrials.gov . Unique identifier: NCT02641431. Abstract : Supplemental Digital Content is available in the text.